2013
DOI: 10.1371/journal.pone.0061776
|View full text |Cite
|
Sign up to set email alerts
|

Is Serum Zinc Level Associated with Prediabetes and Diabetes?: A Cross-Sectional Study from Bangladesh

Abstract: AimsTo determine serum zinc level and other relevant biological markers in normal, prediabetic and diabetic individuals and their association with Homeostasis Model Assessment (HOMA) parameters.MethodsThis cross-sectional study was conducted between March and December 2009. Any patient aged ≥30 years attending the medicine outpatient department of a medical university hospital in Dhaka, Bangladesh and who had a blood glucose level ordered by a physician was eligible to participate.ResultsA total of 280 partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 29 publications
6
32
0
Order By: Relevance
“…At the same time, zinc is a critical component of the catalytic site of .300 enzymes, implicated in synthesis, storage, and secretion of insulin, as well as being a signaling molecule after insulin secretion (5). Some studies have investigated possible associations between zinc status and diabetes; most reported that patients with diabetes had lower serum/plasma zinc levels (6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Interactions Between Zinc Transporter-8 Gene (Slc30a8) and Pmentioning
confidence: 99%
“…At the same time, zinc is a critical component of the catalytic site of .300 enzymes, implicated in synthesis, storage, and secretion of insulin, as well as being a signaling molecule after insulin secretion (5). Some studies have investigated possible associations between zinc status and diabetes; most reported that patients with diabetes had lower serum/plasma zinc levels (6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Interactions Between Zinc Transporter-8 Gene (Slc30a8) and Pmentioning
confidence: 99%
“…A similar study in Iraq noted that receiving 30 mg of Zinc per day for three months for type-2 diabetics has beneficial effects in elevating their serum Zinc level, and in improving their glycemic control that is shown by decreasing their HbA1c concentration [14]. In addition, improved fasting blood glucose levels of up to 30% in patients with cirrhosis through supplementation of Zinc for 2 months has been reported [15]. A recent single blinded trial conducted in Sri Lanka by Gunesekara et al Zinc absorption is also know to be altered in patients with diabetes [13].…”
Section: Introductionmentioning
confidence: 82%
“…In addition, there is particular interest in the idea that oxidative stress is relevant in the pathogenesis of diabetes and its' complications. Impaired synthesis of enzymes, such as superoxide dismutase and glutathione peroxidase, Zinc is a partof these enzymes' structures and its deficiency may impair their synthesis and associated with increased oxidative stress [15]. It has been long known that diabetes is accompanied by hypozincemia [16] and hyperzincuria [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent evidence, including the present study suggests that hypozincaemia is also present even in those with pre-diabetes, hence preceding the onset of Type-2 diabetes. 17 Furthermore, Zinc supplementation has also been shown to improve glucose handling in pre-diabetes. 18 Zinc deficiency is known to have numerous detrimental health effects.…”
Section: Discussionmentioning
confidence: 99%